Tantangan Pengelolaan Perikanan di Indonesia - Sulaiman Sulaiman (Kanun Jurnal Ilmu Hukum, 2010)
ABSTRACT: Fisheries management will determine the sustainability of fisheries resources in Indonesia. The concept of sustainable fisheries management is a response to occupation of the development of growth which lead to increased utilization of fish resources. This paper wants to answer how the concept of the implementation of sustainable fisheries management, as well as its importance for Indonesia. Of solution known that the concept of sustainable fisheries management is applicable in the practical implementation of regulation and the concept of development. This in turn has implications for social justice in fisheries management itself. The Challenge of Fisheries Management in Indonesia